2016
DOI: 10.1186/s12931-015-0316-1
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and IL-1β-activated human mesenchymal stromal cells increase airway epithelial wound healing in vitro via activation of the epidermal growth factor receptor

Abstract: BackgroundMesenchymal stromal cells (MSCs) are investigated for their potential to reduce inflammation and to repair damaged tissue. Inflammation and tissue damage are hallmarks of chronic obstructive pulmonary disease (COPD) and MSC infusion is a promising new treatment for COPD. Inflammatory mediators attract MSCs to sites of inflammation and affect their immune-modulatory properties, but little is known about their effect on regenerative properties of MSCs. This study investigates the effect of the pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 58 publications
5
54
0
3
Order By: Relevance
“…Previous studies have revealed that human MSCs stimulated with pro-inflammatory cytokines (such as TNF-α and IL-1β) can improve the secretory effects of immunomodulatory soluble factors (Broekman et al, 2016;Heo et al, 2011). Here, we also showed that TNF-α-stimulated cAT-MSCs released significantly higher concentrations of TSG-6 (2.5-fold) and PGE2 (3-fold), relative to naive cAT-MSCs.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies have revealed that human MSCs stimulated with pro-inflammatory cytokines (such as TNF-α and IL-1β) can improve the secretory effects of immunomodulatory soluble factors (Broekman et al, 2016;Heo et al, 2011). Here, we also showed that TNF-α-stimulated cAT-MSCs released significantly higher concentrations of TSG-6 (2.5-fold) and PGE2 (3-fold), relative to naive cAT-MSCs.…”
Section: Discussionsupporting
confidence: 71%
“…Fan et al also revealed that human MSCs stimulated with interleukin (IL)-1β showed enhanced efficacy in mice with colitis (Fan et al, 2012). In addition, recent studies have demonstrated that MSCs pre-treated with pro-inflammatory cytokines showed enhanced secretory abilities (Broekman et al, 2016;Heo et al, 2011). However, few studies have assessed the therapeutic effects of pro-inflammatory cytokine-stimulated canine MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this phenomenon was accompanied by elevated, local expression of a range of pro‐inflammatory cytokines, including IL‐6 and TNF‐ α , although not IL‐1 β , which have also been implicated in causing respiratory epithelial cell damage and promoting autoimmunity in patients with COPD …”
Section: Discussionmentioning
confidence: 99%
“…Classically IL-1β is described as an acute phase reactant early during inflammation, but in certain immunologic contexts plays a major role in tissue repair. IL-1β levels may contribute to early bone healing 53 and prime MSCs to promote healing of airway epithelial cells 54 . TGF-β classically is involved in fibrosis and protects cell survival during radiation 55 , structural changes of tissues via EMT and inhibition of cell proliferation 56 , and has a protective role in acute GVHD 57 .…”
Section: Discussionmentioning
confidence: 99%